Minimum Wages in Developing Countries - Tony Fang; Viet Hoang Ha (Institute of Labor Economics (IZA), 2022)
There is considerable debate on the level and effects of minimum wages for many decades. However, most of the studies are conducted in developed countries. This chapter first reviews the theoretical frameworks of anticipated effects of a minimum wage increase on wages and employment in developing countries. The empirical challenges are then discussed, including potential heterogeneity, simultaneity (or endogeneity) between employment and minimum wages, and possible omitted variable bias, taking into consideration of the different labour market structures and labour market institutions in developing countries, particularly the level of informal sector, extent of binding minimum wages, level of enforcement, and the vulnerability of the workers impacted. Evidence from BRICS members (Brazil, Russia, India, China, and South Africa) are reviewed and discussed. Surprisingly, there is substantial evidence of positive wage effects in both formal and informal sectors, although the adverse effects on employment are generally modest in the formal sector, and almost non-existent in the informal sector. However, when minimum wages are binding and enforced, studies focusing on vulnerable workers do find significant and positive wage effects and strong disemployment effects, implying that the classic trade-off of minimum wages between higher wages and lower employment does occur in developing countries.
Keywords: J31; J33; J38; 330; minimum wages; labour market outcomes; developing countries